A single dose of Astragalus saponins adjuvanted inactivated vaccine for pseudorabies virus protected mice against lethal challenge - Chang, Chen; Wang, Haiyan; Hua, Tao; Zhang, Daohua; Hong, Weibin; Deng, Bihua; Tang, Bo (Frontiers in Veterinary Science, 2022)
Pseudorabies (PR) is an important infectious disease of swine that causes enormous economic losses to the swine industry in China. Immunization with vaccines is a routine practice to control this disease. PRV inactivated vaccines usually require a booster vaccination to provide complete immune protection. Therefore, Astragalus saponins (AST) have been added as an immunopotentiator to improve the immune efficacy and reduce the immunization times for the PRV inactivated vaccine. The results in mice have shown that a single dose of AST-adjuvanted PRV inactivated vaccine promoted higher production of gB-specific IgG, IgG1, and IgG2a and neutralizing antibody, secretion of Th1-type (IFN-γ) and Th2-type (IL-4) cytokines, and lymphocyte proliferation than mice immunized without AST. Compared to mice immunized without AST, a single dose of the AST-adjuvanted PRV inactivated vaccine improved the survival percentage of mice and reduced the PRV viral loads in the lungs and brains after lethal challenge. In summary, AST was an effective immunopotentiator to improve the immune efficacy of a single dose PRV inactivated vaccine.